2016
DOI: 10.1016/j.jped.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human milk titratable acidity before and after addition of a nutritional supplement for preterm newborns

Abstract: The study observed no significant differences in Dornic acidity of raw human milk and pasteurized human milk; however, the dilution of a human milk supplementation caused a significant increase in acidity. Further investigations are necessary on the influence of this finding on the quality of supplemented milk and its consequences on the health of preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Pereira et al [31], reported that high and low values for human acidity may in-Results are expressed as mean ± standard deviation, among three batches carried out in triplicate for each freeze concentration stage, with three repetitions for titratable acidity. fluence the biological availability of nutrients, such as calcium, which is essential for bone mineralization in preterm infants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pereira et al [31], reported that high and low values for human acidity may in-Results are expressed as mean ± standard deviation, among three batches carried out in triplicate for each freeze concentration stage, with three repetitions for titratable acidity. fluence the biological availability of nutrients, such as calcium, which is essential for bone mineralization in preterm infants.…”
Section: Resultsmentioning
confidence: 99%
“…fluence the biological availability of nutrients, such as calcium, which is essential for bone mineralization in preterm infants. Therefore, considering the importance of human milk acidity for its nutritional quality, it should be emphasized that acidic or alkaline overloads result in metabolic acidosis or alkalosis, and its use can cause necrotizing enterocolitis in very low birth weight preterm infants [31].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to point out that acidified milk may not meet nutritional requirements and the acidity increase with consequent protons release from the ionization of lactic acid provoke the destabilization of soluble proteins and casein micelles. Such alterations may incite milk coagulation, increase osmolarity and alter taste and odor, as well as impede calcium availability 17 . In addition, lipolytic and proteolytic reactions increase acidity with reduced energetic and immune value of colostrum.…”
Section: Discussionmentioning
confidence: 99%
“…The acidity of raw human milk at the moment of being milked is 1 to 7° Dornic and the lipid content influences the treatable acidity 10 . Changes this parameter may cause acidity or basicity overload and consequently can cause acidosis or metabolic alkalosis, so when breastfed the newborn can develop necrotizing enterocolitis and this can be aggravated especially if the baby is LBW and premature 10,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation